2008
DOI: 10.1097/hjr.0b013e328305df05
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of patient and physician factors to cardiac rehabilitation enrollment: a prospective multilevel study

Abstract: Background-Cardiac rehabilitation (CR) is an established means of reducing mortality, yet is grossly under-utilized. This is due to both health system and patient-level factors, issues which have yet to be investigated concurrently. This study utilized a hierarchical design to examine physician and patient-level factors affecting verified CR enrollment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 44 publications
7
118
1
3
Order By: Relevance
“…CR involves structured exercise training, education, risk factor reduction and behavior change counseling. Participation in CR programs have been shown to reduce mortality by about 25%-30% and to have favorable effects on re-hospitalization and functional capacity (Grace et al, 2008). Emerging evidence supports the feasibility, safety and benefits of CR for transient ischemic attack/mild non-disabling stroke patients as well (Lennon et al, 2008;Prior et al, 2011;Tang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…CR involves structured exercise training, education, risk factor reduction and behavior change counseling. Participation in CR programs have been shown to reduce mortality by about 25%-30% and to have favorable effects on re-hospitalization and functional capacity (Grace et al, 2008). Emerging evidence supports the feasibility, safety and benefits of CR for transient ischemic attack/mild non-disabling stroke patients as well (Lennon et al, 2008;Prior et al, 2011;Tang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…20 the uK is the only country to establish targets for Cr utilization, where the aim is to achieve an 85% referral rate. 21 reasons for low rates of Cr utilization are multifactorial, and include health-system, [22][23][24][25] health-care provider, 7,[26][27][28][29][30][31][32][33][34] and patient level 20,22,26,29,30,[35][36][37] factors. lack of Cr referral is the most common reason given by patients when they are asked why they did not attend Cr after a cardiac event or procedure.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Our findings about referral to CR programmes are somewhat higher than the EuroAspire study (45%) including patients from 22 countries, and with significant differences between the countries. [23] Two US studies [19,23] also reported lower referral rates (43% and 59%). The total CR attendance in our study was similar to the Swedish results in the EuroAspire study (between 40% and 50%) but somewhat higher than other reports.…”
Section: Discussionmentioning
confidence: 99%